2017
DOI: 10.15406/jdhodt.2017.07.00252
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Dental Caries and Periodontal Disease in Deaf and Mute Children Attending Special Schools in Jaipur City, Rajasthan

Abstract: Introduction: Oral health of special children is one of the sensitive issues that have been touched by very few people. An attempt has been made to assess the prevalence of dental caries and periodontal disease status in deaf and mute children. Materials and method: A total of 257 deaf and mute children were included from the four special schools in Jaipur city. Dental caries and periodontal disease status was recorded. Data thus collected subjected to statistical analysis using frequency distribution. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 10 publications
2
5
1
Order By: Relevance
“…The present study found that more than half of our study participants had bleeding on probing which is consistent with studies done in Nigeria [18] and India [28]. The high prevalence of periodontal disease in disabled schoolchildren might be due to the challenges in oral hygiene practice or lack of proper family support during tooth brushing.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The present study found that more than half of our study participants had bleeding on probing which is consistent with studies done in Nigeria [18] and India [28]. The high prevalence of periodontal disease in disabled schoolchildren might be due to the challenges in oral hygiene practice or lack of proper family support during tooth brushing.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, 50% of intellectually disabled individuals in Hyderabad, India had gingivitis [26]. However, our finding is high compared with studies done in Nigeria (7.3%) [18], Taiwan (5.4%) [27], and India (2.72%) [28]. The difference might be due to the socioeconomic difference and because of the use of different methods for diagnosing periodontal disease.…”
Section: Discussioncontrasting
confidence: 71%
“…The sample size of 106 participants was obtained by using open epi online sample size calculator. The statistics considered for sample size estimation was dental caries as 30.74% 11 , margin of error as 8.8% and 95% confidence level. The non-probability purposive sampling technique was employed.…”
Section: Methodsmentioning
confidence: 99%
“…Possible reasons for findings in the study might be because children with physical disabilities know little about their oral health; also experience considerably higher levels of oral health diseases and greater food debris and also more difficulty for accessing oral health care. 50 According to a study done in 2015 by Pradhan M, et al among hearing impaired adults reported that periodontal index was 0.38±0.74 20 and another study done in 2010 by Rawlani S, et al among deaf and mute children reported periodontal index to be 0.42±0.32. The probable reason stated was lack of oral hygiene education among disabled groups.…”
Section: Periodontal Disease Among Visually and Hearing Impaired Individualsmentioning
confidence: 99%
“…25 A study conducted in 2010 by Jain M, et al among deaf and blind children and adults reported that 32% participants were periodontally healthy while the remaining participants had shallow and deep pockets and higher percentage of blind participants that is 43% were periodontally healthy than 24% of hearingimpaired participants. 50 The reason for the poor periodontal health of hearing-impaired participants as compared to blind participants was due to lack of treatment among the former group. A study done in 2012 by Ameer N, et al among special needs teenagers reported that 32% physically handicapped participants had loss of attachment with 4-5mm pockets and 7% in intellectually disabled population.…”
Section: Periodontal Disease Among Visually and Hearing Impaired Individualsmentioning
confidence: 99%